PROBLEMATIKA PEMBELAJARAN BAHASA INDONESIA MEMBACA PEMAHAMAN DI SEKOLAH DASAR: SEBUAH TELAAH PUSTAKA - Setya Ratna Dianuri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research writing emerged because of problems in learning Indonesian, especially in reading comprehension skills in elementary school students. This article discusses: 1) what are the objectives of reading comprehension; 2) what are the factors that influence reading comprehension; 3) what are the problems in reading comprehension; 4) how are the solutions to reading comprehension problems. The research method for reading comprehension problems uses the library research method, namely by looking for theories about reading comprehension skills and relevant theories. The results of the research in this article are the identification of reading comprehension problems according to Rahayu et al., which include students' lack of understanding in answering questions with the 5W + 1H elements, difficulty in determining the main sentence, and students' difficulty in drawing conclusions from reading. However, not only discussing what the problems are in learning reading comprehension, the author also adds a discussion of the factors that influence reading comprehension and solutions to these problems.